Management Safety Healthy Work dalam Upaya Meminimalkan Kecelakaan Kerja di Pt Huawei Tech Investment: Management Safety Healthy Work dalam Upaya Meminimalkan Kecelakaan Kerja di Pt Huawei Tech Investment - SU, LIAN GANG; Sukamdani, Hariyadi; Maharani, Maya Dewi Diyah (Fakultas Ekonomi Universitas Kadiri, 2024)
This research aims to understand the strategies implemented by companies to minimize work accidents and support a safe and healthy work environment at PT. Huawei Tech Investment Indonesia uses the ISM method and PDCA method. Qualitative and quantitative approaches with descriptive research type data collection for three months, using primary and secondary data collection techniques. This study found that the PDCA method is integral to PT's safety and health work program. Huawei Indonesia. The results of research conducted by PT. Huawei Indonesia is committed to prioritizing the safety and welfare of employees within the organization. The company follows a structured approach in planning, implementing, monitoring, and adjusting safety measures to ensure continuous improvement and excellent compliance with K3 standards.